PD-L1 Immunohistochemistry Assay Comparison in Atezolizumab Plus nab-Paclitaxel–Treated Advanced Triple-Negative Breast Cancer. (7th June 2021) - Rugo, Hope S; Loi, Sherene; Adams, Sylvia; Schmid, Peter; Schneeweiss, Andreas; Barrios, Carlos H; Iwata, Hiroji; Diéras, Véronique; Winer, Eric P; Kockx, Mark M; Peeters, Dieter; Chui, Stephen Y; et al.
Abstract: Background: In the phase III IMpassion130 study, atezolizumab plus nab -paclitaxel (A+nP) showed clinical benefit in advanced or metastatic triple-negative breast cancer patients who were programmed death-ligand 1 (PD-L1)+ (tumor-infiltrating immune cells [IC] ≥1%) using the SP142 immunohistochemistry assay. Here we evaluate 2 other PD-L1 assays for analytical concordance with SP142 and patient-associated clinical outcomes. Methods: Samples from 614 patients (68.1% of intention-to-treat population) were centrally evaluated by immunohistochemistry for PD-L1 status on IC (VENTANA SP142, SP263, Dako 22C3) or as a combined positive score (CPS; 22C3). Results: Using SP142, SP263, and 22C3 assays, PD-L1 IC ≥1% prevalence was 46.4% (95% confidence interval [CI] = 42.5% to 50.4%), 74.9% (95% CI = 71.5% to 78.3%), and 73.1% (95% CI = 69.6% to 76.6%), respectively; 80.9% were 22C3 CPS ≥1. At IC ≥1% (+), the analytical concordance between SP142 and SP263 and 22C3 was 69.2% and 68.7%, respectively. Almost all SP142+ cases were captured by other assays (double positive), but several SP263+ (29.6%) or 22C3+ (29.0%) cases were SP142– (single positive). A+nP clinical activity vs placebo+nP in SP263+ and 22C3+ patients (progression-free survival [PFS] hazard ratios [HRs] = 0.64 to 0.68; overall survival [OS] HRs = 0.75 to 0.79) was driven by double-positive cases (PFS HRs = 0.60 to 0.61; OS HRs = 0.71 to 0.75) rather than single-positive cases (PFS HRs = 0.68 to 0.81; OS HRs = 0.87 to 0.95). Concordance for harmonized cutoffs for SP263 (IC ≥4%) and 22C3 (CPS ≥10) to SP142 (IC ≥1%) was subpar (approximately 75%). Conclusions: 22C3 and SP263 assays identified more patients as PD-L1+ (IC ≥1%) than SP142. No inter-assay analytical equivalency was observed. Consistent improved A+nP efficacy was captured by the SP142 PD-L1 IC ≥1% subgroup nested within 22C3 and SP263 PD-L1+ (IC ≥1%) populations.